Media Digital Sebagai Upaya Optimalisasi Keterampilan Menyimak Anak Berkebutuhan Khusus - Chusna Arifah; Cece Rakhmat; Sima Mulyadi (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2023)
Adequate education services are the right of all citizens of the Unitary Republic of Indonesia, including children with special needs. One of the basic human capitals to be able to become a respectable human being is seen from listening skills. Because listening skill is a self of value that must radiate as a form of self as a social being. Listening skills in children with special needs are a fundamental area that is rarely touched upon in any research context. The Indonesian Education University's laboratory elementary school in this context has attempted to provide inclusive school services for children with special needs, however these efforts have only been made in this study. The solution taken to solve this problem is to apply digital media which is seen as having high value and attractiveness for children with special needs who want to improve their listening skills. The results of this preliminary research show that Android digital media can be applied to simulate and optimize the listening skills of children with special needs.